(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Oral route is one of the most popular and successful delivery routes for the medicines. It achieved a prominent place in drug delivery due to ease of administration by all age groups. The major disadvantage of oral conventional drug therapy is that, it has to be taken 2–3 times a day, and if patient misses any dose it leads to incomplete prescribed dose and delays the time of cure. The considerable efforts have been taken to improve the success rate of oral drug delivery by modifying various parameters related to drug release. Osmosis is the movement of a substance against concentration gradient; in this instance, osmotic delivery use an osmotic gradient to successfully distribute the drug in controlled way and with zero order kinetics and emerging as the most dependable method of regulated drug delivery. The medication release from device is mostly unaffected by stomach secretions. Drug, release control polymer, osmotic agent, semipermeable membrane, and delivery orifice are the major parts of osmotic delivery system. This review mainly focuses on an osmotic drug delivery system providing detailed information regarding its design, different types, and responsible ingredients for controlled release by the virtue of osmosis.